Experimental Investigation into Vibration Characteristics for Damage Minimization in a Lapping Process - J. Suwatthikul; S. Sornmuang; T. Yaemglin; I. Cheowanish; C. Supavasuthi (Shock and Vibration)
Lapping machines are used in a hard disk rough lapping process where a workpiece (a wafer row bar) is locked with a robot arm and rubbed on a lap plate. In this process, the lap plate’s condition and lifetime are among important concerned factors. The lifetime can be too short due to the plate being accidentally scratched by the workpiece during lapping. This problem leads to undesired consequences such as machine downtime and excessive plate material usage. This paper presents an experimental investigation into vibration characteristics of passed and failed lapping scenarios and discusses a potential solution to minimize the serious damage so-called “plate scratch” which intermittently occurs in such process. The experimental results show that, by in situ monitoring vibration and utilizing artificial intelligence, damage minimization can be possible.